The relationship between hemogram parameters and mortality in neonatal calves with diarrhea - Merve Ider; Amir Naseri; Alper Erturk (Eurasian Journal of Veterinary Sciences)
Aim: The objective of the present study was to reveal the relationship between hemogram parameters and mortality in neonatal calves with diarrhea from different etiological origins. Materials and Methods: Fifty calves with diarrhea were enrolled in the study. The calves were divided into 2 groups as surviving and non-surviving calves. In addition, on the basis of the stool quick test and etiological agent, it was divided into 3 subgroups: bacterial (E. coli), viral (rotavirus and coronavirus), and parasitic (Cryptosporidium parvum). Total leukocyte (WBC), lymphocyte (Lym), monocyte (Mon), granulocyte (Gra), erythrocyte (RBC), mean corpuscular volume (MCV), hematocrit (HCT), mean corpuscular hemoglobin (MCH), mean corpuscular hemoglobin concentration (MCHC), red blood cell distribution width (RDW), hemoglobin (Hb), and thrombocyte (PLT) were measured. Results: Regardless of etiology, MCHC levels of non-surviving calves were lower than those of surviving calves (cut-off: 32.15 g/dL, 68% sensitivity, 62% specificity, p = 0.041). Also, MCHC levels of non-surviving calves with viral etiology were lower than those of surviving calves (cut-off: 31.75 g/ dL, 85% sensitivity, 75% specificity, p = 0.029). RBC levels of non-surviving calves with E. coli etiology were lower than those of surviving calves (cut-off: 9.27 ×103 cells/mL, 83% sensitivity, 84% specificity, p = 0.024). There was no statistically significant difference in hemogram parameters of calves infected with C. parvum. Conclusion: MCHC and RBC levels were statistically significant in the estimation of mortality in neonatal calf diarrhea. The evaluation of hemogram parameters together with other blood parameters (blood gas, etc.) may be more useful in estimating mortality.